Pharmacodynamics of zoliflodacin plus doxycycline combination therapy against Neisseria gonorrhoeae in a gonococcal hollow-fiber infection model - Jacobsson, Susanne; Golparian, Daniel; Oxelbark, Joakim; Kong, Fabian Y. S.; Da Costa, Renata Maria Augusto; Franceschi, Francois; Brown, David; Louie, Arnold; Drusano, George; Unemo, Magnus (Frontiers in Pharmacology, 2023)
Antimicrobial resistance in Neisseria gonorrhoeae compromises the management of gonorrhea globally. Novel antimicrobials for gonorrhea treatment are imperative. Zoliflodacin (spiropyrimidinetrione, DNA Gyrase B inhibitor) recently showed non-inferiority compared to recommended treatment in its phase III randomized controlled clinical trial. Doxycycline, the first-line treatment for chlamydia and empiric treatment for non-gonococcal urethritis, will likely be frequently given together with zoliflodacin. In this study, our dynamic in vitro Hollow Fiber Infection Model (HFIM) was used to investigate combination therapies with zoliflodacin and doxycycline. Dose-range experiments using the three gonococcal strains WHO F (susceptible to relevant antimicrobials), WHO X (extensively drug-resistant, including ceftriaxone resistant; zoliflodacin-susceptible) and SE600/18 (zoliflodacin-susceptible strain with GyrB S467N substitution) were conducted simulating combination therapy with a single oral dose of zoliflodacin 0.5-4 g combined with a doxycycline daily oral dose of 200 mg administered as 100 mg twice a day, for 7 days (standard dose for chlamydia treatment). Comparing combination therapy of zoliflodacin (0.5-4 g single dose) plus doxycycline (200 mg divided into 100 mg twice a day orally, for 7 days) to zoliflodacin monotherapy (0.5-4 g single dose), showed that combination therapy was slightly more effective than monotherapy in N. gonorrhoeae killing and zoliflodacin resistance suppression. Accordingly, WHO F was eradicated by only 0.5 g single dose of zoliflodacin in combination with doxycycline and WHO X and SE600/18 were both eradicated by a 2 g single dose of zoliflodacin in combination with doxycycline, and no zoliflodacin-resistant populations occurred during the seven-day experiment when using this zoliflodacin dose. When using suboptimal (0.5-1 g) zoliflodacin doses together with doxycycline, gonococcal mutants with increased zoliflodacin MICs, due to GyrB D429N and the novel GyrB T472P, emerged, but both these mutants had an impaired biofitness. The present study shows the high efficacy of zoliflodacin plus doxycycline combination therapy using a dynamic HFIM that more accurately and comprehensively simulate gonococcal infection and their treatment, i.e., compared to static in vitro models, such as short-time checkerboard experiments or time-kill curve analysis. Based on our dynamic in vitro HFIM work, zoliflodacin plus doxycycline for treatment of both gonorrhea and chlamydia can be an effective combination.